Moldability of nano size zirconia for powder injection molding process by using PEG and PMMA binders - Al Basir,; Abu Bakar Sulong,; Etta Eshak,; Najlaa Nazihah Mas’ood,; Nashrah Hani Jamadon,; Norhamidi Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Powder injection molding (PIM) is a well-known manufacturing technique for the production of metal and ceramic near net shapes. Now-a-days, this technology is largely used in electronics, biomedical, aerospace, automotive, defence and telecommunication industries. In this paper, green parts of ZrO2 with polyethylene glycol (PEG), polymethyl methacrylate (PMMA) and stearic acid (SA) binders were prepared by PIM process. The average particle size of ZrO2 powder was 50 nm with pycnometer density of 6.054 g/cm3. The ZrO2 powder was mixed with binder content of 73 wt.% PEG, 25 wt.% PMMA and 2 wt.% SA. The rheological results showed pseudoplastic properties of the feedstock at 140 °C and 160 °C, which was suitable for PIM process. The suitable injection molding parameters for feedstock at 51 vol.% powder loading such as mold temperature, injection temperature, injection pressure and holding time were 60 °C, 160 °C, 10 bar and 8 s, respectively. At the same powder loading, the green part density of 3.60 g/cm3 was measured, whereas for the three-point flexural, the measured strength was in the range of 13-15 MPa. For structural analysis, the morphological properties of the powder as well as the surface and the cross-section of the green part was examined.